Investigating the Influence of Process Parameters on the Mechanical Properties of Extruded Aluminum Tubes by Cyclic Indentation Tests - David Görzen; Florian Patrick Schäfke; Bastian Blinn; Christian Klose; Hans Jürgen Maier; Tilmann Beck (Metals, 2021)
Given the complex process condition, extruded aluminum (Al) alloy tubes show locally pronounced differences in microstructure and mechanical properties, which can be influenced by subsequent heat treatment. In the present study, cyclic indentation tests (CITs) were conducted on extruded Al alloy EN AW-6082 to locally determine hardness and cyclic hardening potential, which was complemented with light optical microscopy. To analyze the influence of extrusion process and subsequent heat treatment, the EN AW-6082 tubes investigated were manufactured with extrusion ratios Ψ of 13:1 and 22:1, both in as-extruded and T6 heat-treated conditions. The results obtained for the as-extruded state showed significant differences of the local mechanical properties and demonstrated that an increased Ψ leads to higher hardness, caused by more pronounced plastic deformation during the manufacturing process. Moreover, an increase of hardness and cyclic hardening potential was observed after a T6 heat treatment, which also reduced the difference in hardness between the different extrusion ratios. Additionally, the pronounced local differences in hardness and cyclic hardening potential correlated with the local microstructure. The results demonstrated that CITs enable the analysis of local mechanical properties of extruded EN AW-6082 profiles, resulting from different extrusions ratios as well as subsequent heat treatment.